2022
DOI: 10.1038/s41570-021-00345-7
|View full text |Cite|
|
Sign up to set email alerts
|

Natural product anticipation through synthesis

Abstract: Natural product synthesis remains one of the most vibrant and intellectually rewarding areas of chemistry, although the justifications for pursuing it have evolved over time. In the early years, the emphasis lay on structure elucidation and confirmation through synthesis, as exemplified by the celebrated studies on cocaine, morphine, strychnine and chlorophyll. This was followed by a phase where the sheer demonstration that highly complex molecules could be recreated in the laboratory in a rational manner was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 112 publications
1
38
1
Order By: Relevance
“…This compound had NMR spectra that were identical with those reported for emerione C (Figure 3B, Table S3), strongly indicating that emerione C shares the same stereochemical backbone configuration as emerione A. To unambiguously clarify the chemical structures, we solved the structure of 50 by X-ray crystallography (Figure 3C), and found that it has the structure that was originally proposed for emerione C. We, therefore, reassign the structure of emerione C (49) as it is depicted in Scheme 2 and name compound 50, which we think is not unlikely to also be a natural product, (+)-emerione D. [23] In order to gain deeper insight into the stereochemical outcome of the 8/6 electrocyclization cascade, density functional theory (DFT) calculations were employed at the SMD(toluene)-M06-2X/Def2-TZVP//M06-2X/Def2-SVP level of theory. The calculations reveal that the two transition states (TS-1 and TS-2) leading from pentaene 9 to vinylcyclooctatrienes 47 and 48, respectively, are nearly isoenergetic as are 47 and 48 themselves (Figure 4, Figure S4).…”
mentioning
confidence: 85%
“…This compound had NMR spectra that were identical with those reported for emerione C (Figure 3B, Table S3), strongly indicating that emerione C shares the same stereochemical backbone configuration as emerione A. To unambiguously clarify the chemical structures, we solved the structure of 50 by X-ray crystallography (Figure 3C), and found that it has the structure that was originally proposed for emerione C. We, therefore, reassign the structure of emerione C (49) as it is depicted in Scheme 2 and name compound 50, which we think is not unlikely to also be a natural product, (+)-emerione D. [23] In order to gain deeper insight into the stereochemical outcome of the 8/6 electrocyclization cascade, density functional theory (DFT) calculations were employed at the SMD(toluene)-M06-2X/Def2-TZVP//M06-2X/Def2-SVP level of theory. The calculations reveal that the two transition states (TS-1 and TS-2) leading from pentaene 9 to vinylcyclooctatrienes 47 and 48, respectively, are nearly isoenergetic as are 47 and 48 themselves (Figure 4, Figure S4).…”
mentioning
confidence: 85%
“…This remarkable bond reorganization delivers an original strictosidine-derived skeleton which is not a natural product or yet to be discovered from natural sources. 29 In order to form indolopyridone 52 and prevent the spontaneous Diels-Alder cycloaddition, the cyclodehydratation had to be performed at a lower temperature (80 °C) after which, removal of the four acetates with methanol and potassium carbonate led to ophiorrhiside E 6a in 30% over two steps (Scheme 5). At 80 °C, the conversion of (−)-50a into 52 is modest since 57% of ophiorrhine F 7a was also isolated.…”
Section: Scheme 4 Attempts Towards the Synthesis Of The Indolopyridon...mentioning
confidence: 99%
“…Pleasingly, NMR data for 17 fully matched that for natural hyperelodione D, thus proving our structural reassignment of this complex meroterpenoid. The prenyl/geranyl substitution pattern of 17 and 26 was established by HMBC correlations and comparison to NMR data for erectones A and B. Alongside the Diels–Alder adducts 19 , 23 , 24 and 25 , it is also probable that tetracycle 26 occurs in nature, and our characterization of these compounds could aid their future discovery in Hypericum plants [24] . Finally, the Diels–Alder cascade between erectquione A and E ‐β‐ocimene was also conducted in 10 % aq.…”
Section: Figurementioning
confidence: 99%
“…The prenyl/geranyl substitution pattern of 17 and 26 was established by HMBC correlations and comparison to NMR data for erectones A and B. Alongside the Diels-Alder adducts 19, 23, 24 and 25, it is also probable that tetracycle 26 occurs in nature, and our characterization of these compounds could aid their future discovery in Hypericum plants. [24] Finally, the Diels-Alder cascade between erectquione A and E-β-ocimene was also conducted in 10 % aq. HCl at 50 °C to give erectones A and B in 40 % yield, alongside the Diels-Alder adducts.…”
mentioning
confidence: 99%